THE ANALYSIS OF PRESUPPOSITION IN THE SHORT STORIES OF SILVESTER GORIDUS SUKUR - Erwin Oktoma; Styfanus Mardiyono (English Review: Journal of English Education, 2013)
Abstract: This paper is descriptive qualitative which describes the types of presuppositions and their meaning in the short stories by Silvester Goridus Sukur. The research questions of this paper are; What are the types of presupposition and dominant type of presupposition in the short stories by Silvester Goridus Sukur. In order to analyze the data, the writer employs Yule’s theory which divides presupposition into 6 types: existential presupposition, factive presupposition, lexical presupposition, structural presupposition, non-factive presupposition and counterfactual presupposition. The data of the research are sentences which contains presupposition triggers. The results of this study shows that based on Yule’s theory, it has been found that there are 219 presuppositions. 129 existential presuppositions or 58,90 %, 47 lexical presuppositions or 21,56 %, 9 structural presuppositions or 4,10 %, 15 factive presuppositions or 6,84 %, 7 non factive presuppositions or 3,19 % and 3 counterfactual presuppositions or 1,36 %.Keywords: Presupposition, type of presupposition, presupposition triggers, short stories of Silvester Goridus Sukur.